The School of Traditions and Modern Chalanges - Kokiel, Andrzej (Pedagogical Discourse, 2012)
This publication presents the problems of the school that have been included in the process of change caused by civilization development. These trends have been presented in relation to the functions implemented in these institutions in terms of contemporary challenges and social expectations.